2017
DOI: 10.5014/ajot.2017.025015
|View full text |Cite
|
Sign up to set email alerts
|

Do Neglect Assessments Detect Neglect Differently?

Abstract: OBJECTIVE. We determined whether various assessment tools detect neglect differently by administering a battery of assessments to people with stroke. METHOD. We conducted a case series study and administered five neglect assessments (paper-and-pencil, functional, virtual reality) to participants poststroke. RESULTS. Twelve participants (6 men, 6 women) with stroke completed the assessment battery, which required approximately 2 hr to administer (over one to two sessions). All part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 35 publications
1
29
0
Order By: Relevance
“…The CBS is a functional neglect assessment because it assesses neglect through observation of activities such as eating and locomotion (i.e., collisions, navigation items). The CBS has items that assess for personal, peripersonal, and extrapersonal neglect and the type of neglect each item assesses has been delineated (Grattan & Woodbury, 2017; Plummer, Morris, & Dunai, 2003). Assessors score 10 items using a 4-point scale (Azouvi, 1996).…”
Section: Methodsmentioning
confidence: 99%
“…The CBS is a functional neglect assessment because it assesses neglect through observation of activities such as eating and locomotion (i.e., collisions, navigation items). The CBS has items that assess for personal, peripersonal, and extrapersonal neglect and the type of neglect each item assesses has been delineated (Grattan & Woodbury, 2017; Plummer, Morris, & Dunai, 2003). Assessors score 10 items using a 4-point scale (Azouvi, 1996).…”
Section: Methodsmentioning
confidence: 99%
“…Approximately, 50% of patients who suffered from right-brain stroke manifest unilateral spatial neglect (USN), a complex and heterogeneous attentional-perceptual syndrome characterized by a difficulty or inability to pay attention, detect, and orient toward stimuli presented in the contralesional side (Heilman, et al, 2000 ; Tsirlin et al, 2009 ; Pedroli et al, 2015 ; Rode et al, 2017 ; Zigiotto et al, 2020 ). USN can be divided into several subcategories, depending on whether the behavior is elicited by a sensory, motor, or representational modality, or whether it involves one’s peripersonal, extra-personal, or spatial representation (Plummer et al, 2003 ; Buxbaum et al, 2004 ; Grattan and Woodbury, 2017 ). Thus, USN can also be referred to as visuospatial neglect (VSN), visual neglect (VN), and hemispatial neglect (HSN).…”
Section: Introductionmentioning
confidence: 99%
“…Patients’ impaired judgment of distances from objects could also reflect an ipsilesional shift of their subjective midline, which acts as a framework for goal-directed walking and spatial orientation (Karnath et al, 1991 ; Richard et al, 2004 ; Aravind and Lamontagne, 2018 ). USN patients also tend to miss words while reading (Kim et al, 2015 ; Sugihara et al, 2016 ; Yasuda et al, 2017 , 2018 ), and present a reduced ability to manage both basic and instrumental activities of daily living (BADL and IADL, respectively), such as autonomously bathing or grocery shopping (Buxbaum et al, 2004 ; Grattan and Woodbury, 2017 ). Furthermore, USN patients manifest different degrees of unawareness of their impairments (i.e., anosognosia) and this condition is associated with motor, cognitive, and sensory deficits.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we propose making a distinction between static tests, with low levels of cognitive demand, and dynamic tests, with high levels of cognitive demand. It is not simply the case that dynamic tests are more challenging than static tests, as extensive research has showed dissociations between performances on static versus dynamic tests (Azouvi, 2002;Azouvi et al, 2006;Grattan & Woodbury, 2017;Hamilton et al, 2008). For example, patients may show VSN on the MAC or a Virtual Reality test, but not on a cancellation test, and vice versa (Azouvi et al, 2006;Grech et al, 2017;Peskine et al, 2011;Spreij et al, 2020;Ten Brink et al, 2018).…”
Section: Introductionmentioning
confidence: 99%